Psychosocial risk factors and work performance of chemical manufacturing industry workers - Nuruzzakiyah, Mohd Ishanuddin (2021)
The deterioration of mental health well-being among the working population has become an issue recently. One of the possible assumptions regarding this issue is the existent of psychosocial risk at the workplace. This particular risk can induce a worker's negative physical and emotional state, which can lead to poor work performance. Thus, tending to research on psychosocial risk is significant at the workplace. In association with that, in the Malaysian working context, the manufacturing sector was recorded as the prominent industry with an alarming occurrence of occupational accidents compared to other industries. This notable statistic led to the assumption of the potential existent of psychosocial risk to be one of the contributing risk factors to the occurrence of occupational accidents in the manufacturing plant. Considering there was limited established instrument to investigate the psychosocial risk factors incorporated with work performance factors, an instrument was developed. This study aim to investigates the correlation between two main variables: psychosocial risk factors and work performance factors other than to determine significant risk factors that can affect the workers wellbeing at work. A questionnaire was made by adapting and adopting the construct from three different generic questionnaires. The validity and reliability were tested to the questionnaire that was adapted and adopted from Copenhagen Psychosocial Questionnaire (COPSOQ III), NIOSH Generic Job Stress Questionnaire, and Individual Work Performance Questionnaire (IWPQ 1.0). Then, it was tested for construct validity using Exploratory Factor Analysis (EFA). The results showed that the identified ten psychosocial risk factors and work performance were reduced into eight factors understudy after conducting factor analysis by Principal Component Analysis as a dimensional reduction method. Besides, using mean analysis and Kruskal-Wallis test to determine the significant psychosocial risk factors present in a manufacturing plant. The risk factors presented include the workers perceived as having high job demand (Mean= 3.42). However, job control (Mean= 2.95) and job content (Mean=3.21) were somehow at a moderate level. While, career development (Mean=4.03), interpersonal (Mean= 4.07), and environmental (Mean=2.52) factors were notably as good among the workers. Besides, both task and contextual performance (Mean= 3.73) are considered as excellent as well with minimal negative work behaviour (Mean= 1.86). Next, the significant factors that were significantly different with work performance factors include Interpersonal (p =0.07), Job control (p= 0.008), Career development (p= 0.000), Environment (p= 0.000) and Job content (p= 0.001). Then, The correlation analysis was tested between psychosocial factors and work performance factors using Spearman’s rho. Meanwhile, the significant factors that were associated with work performance factors were Interpersonal (r =0.152, p <0.05), Career development (r =0.243, p < 0.05), Environment (r = 0.237, p < 0.05), and Job demands (r =0.200, p < 0.05). This shows that there was a weak positive correlation (r = 0.1-0.39) between psychosocial risk factors and work performance at a 0.05 level of significance. In sum, this study provides baseline data for future research purposes regarding psychosocial risk factors that incorporated work performance in the study.